Typology of Peri-Urban Farming Households in the Tahoua Region, Niger Republic - Moussa Dit Kalamou, Mahamadou; Ludovic, Andres; Boubacar, Yamba; Philippe, Lebailly (European Scientific Journal, ESJ, 2023)
This paper presents a typology of peri-urban farming households in the Tahoua region of Niger. These farms are managed by peri-urban households distributed according to the agroecological zones of this region. The results were obtained from surveys conducted in five villages with 21 heads of household per village, giving 105 heads of household located in the urban communes of the Tahoua region. The objective of this paper is to highlight, through the analysis of the results, the issues of urbanization of the rural sector, marital status, level of education, granary capacity, different food productions, labor force, and composition in the peri-urban areas of the emerging and agro-ecological UBT. The study will establish a diagnosis of these areas around the secondary cities of Tahoua. The tests of normality and equality of variances allowed us to establish an ANOVA between the agroecological and emergent peri-urban zones. A high percentage of household heads have been found to be illiterate. It stands for peri-urban agricultural, agro-pastoral, and pastoral areas at 55%, 45%, and 43% respectively. Finally, the demographic pressure of the peri-urban agropastoral zone causes a decrease in the average surface areas of the plots.